PKCα Binds G3BP2 and Regulates Stress Granule Formation Following Cellular Stress - Kobayashi, Tamae; Winslow, Sofia; Sunesson, Lovisa; Hellman, Ulf; Larsson, Christer (PLOS ONE, 2012)
Protein kinase C (PKC) isoforms regulate a number of processes crucial for the fate of a cell. In this study we identify previously unrecognized interaction partners of PKCα and a novel role for PKCα in the regulation of stress granule formation during cellular stress. Three RNA-binding proteins, cytoplasmic poly(A)+ binding protein (PABPC1), IGF-II mRNA binding protein 3 (IGF2BP3), and RasGAP binding protein 2 (G3BP2) all co-precipitate with PKCα. RNase treatment abolished the association with IGF2BP3 and PABPC1 whereas the PKCα-G3BP2 interaction was largely resistant to this. Furthermore, interactions between recombinant PKCα and G3BP2 indicated that the interaction is direct and PKCα can phosphorylate G3BP2 in vitro. The binding is mediated via the regulatory domain of PKCα and the C-terminal RNA-binding domain of G3BP2. Both proteins relocate to and co-localize in stress granules, but not to P-bodies, when cells are subjected to stress. Heat shock-induced stress granule assembly and phosphorylation of eIF2α are suppressed following downregulation of PKCα by siRNA. In conclusion this study identifies novel interaction partners of PKCα and a novel role for PKCα in regulation of stress granules.